Abnormal Return And Stock Price Changes Before And After The "Trump Liberation Day" In Indonesia’s Footwear And Garment Subsectors: Evidence From BIMA, ERTX, And GJTL - Muhammad Rijal Alim Rahmat (International Journal of Education Management and Religion, 2026)
International trade policy shifts often trigger a repricing of risk in equity markets, especially for export- and import-oriented industries. Daily event studies are commonly used to test short-run market reactions to well-defined events because they can extract abnormal returns (AR) from broad market dynamics using a simple yet reliable specification (e.g., the market model) (Brown & Warner, 1985; MacKinlay, 1997; Corrado, 1989). On 2 April 2025, the U.S. administration announced a tariff package widely referred to as “Liberation Day.” A universal 10% tariff became effective 5 April 2025 (12:01 a.m. EDT), followed by personalized reciprocal tariffs for major-deficit partners effective 9 April 2025 (12:01 a.m. EDT). For Indonesia, the measures are relevant for footwear and garment subsectors with U.S. export linkages. Around these dates, the Jakarta Composite Index suffered a sharp decline and a brief trading halt on 8 April 2025—an aggregate shock motivating robustness windows around 2/5/9 April to disentangle policy signals from turbulence. While policy briefs discuss macro implications, stock-market evidence for Indonesian issuers remains limited. We fill this gap by testing stock-price reactions for BIMA, ERTX, and GJTL across Short, Mid, and Long windows, and by complementing parametric tests with Corrado’s nonparametric rank test (Corrado, 1989). This study examines abnormal returns and stock price changes around the Trump “Liberation Day” for three Indonesian issuers—BIMA (footwear), ERTX (garment), and GJTL (tyre/rubber). We employ a daily event-study with the market model (OLS) across Short [−3,+3], Mid [−15,+15], and Long [−45,+45] horizons, plus robustness windows (t₀=5 and 9 April 2025) and the nonparametric Corrado rank test. Cross-issuer mean CARs are not statistically significant on all horizons for the main and robustness dates; combined Corrado tests are also insignificant. Issuer-level results show BIMA negative, ERTX positive in the long horizon, and GJTL near zero, suggesting no systematic aggregate abnormal performance during the examined period.